Adverse events and modes of failure related to the FilterWire EZ Embolic Protection System: Lessons learned from an analytic review of the FDA MAUDE database. Issue 1 (15th April 2019) - Khalid, Nauman; Javed, Hasan; Rogers, Toby; Hashim, Hayder; Shlofmitz, Evan; Chen, Yuefeng; Khan, Jaffar M.; Musallam, Anees; Torguson, Rebecca; Bernardo, Nelson L.; Waksman, Ron
Abstract: Objectives: To assess the commonly reported complications and failure modes for FilterWire EZ Embolic Protection Devices (EPD) by analyzing the postmarketing surveillance data from the Food and Drug Administration (FDA) Manufacturer and User Facility Device Experience (MAUDE) database. Background: EPDs prevent distal embolization of atheroembolic materials during percutaneous interventions resulting in reduced microvascular obstruction and improved microcirculation while maintaining tissue perfusion. The FilterWire EZ EPD (Boston Scientific, Natick, MA) is approved for use in interventions of de novo saphenous vein grafts (SVG) and carotid artery stenosis. Robust data on the commonly reported complications and failure modes associated with the FilterWire EZ device are limited. Methods: The MAUDE database was queried from September 1, 2008, through September 30, 2018, for FilterWire EZ system, yielding 474 reports. After exclusion of duplicate and incomplete reports, 464 device reports were included in the final analysis. Results: Device‐related adverse events were most commonly reported for carotid ( n = 281) and SVG ( n = 101) interventions. The most commonly reported major complications were: ischemic stroke ( n = 57), vessel perforation or dissection ( n = 12), death ( n = 8), and myocardial infarction ( n = 5). Minor complications included: hypotension ( n = 68), bradycardia ( n = 41), and vasospasm ( n = 27). The most commonly reported failure modes were: detachment and/or damage of the device components ( n = 118), device entrapment ( n = 90), and stent‐related issues ( n = 46). Conclusions: Analysis of the MAUDE dataset is helpful in identifying the commonly reported adverse events and failure modes of FilterWire EZ devices. This platform serves as an important tool for both physicians and manufacturers to optimize device performance and clinical outcomes.